An Analysis of Curriculum Development for Economics: A Study on Senior High School Economics Subjects - Jun Surjanti; A F Prakoso; H Musfidah; P U Kamalia (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study investigated the material structure of new curriculum development for the Economics subject, focusing on a logical rationale approach to enhance the material structure by including necessary information. This study employed a qualitative methodology, utilising a literary review. The objects were newly designed teaching materials for the Economics subject in senior high schools. Data were gathered via documentation and critical analysis as data processing methods. The study revealed that implementing a newly established curriculum resulted in enhanced quality of economic materials among senior high school pupils, positively impacting their academic performance. The modifications made to the Economics curriculum in senior high school ensured that students acquired the necessary foundational knowledge for advanced learning, eliminating any inconsistencies in prerequisite material. The findings demonstrated that aligning the structural modifications of the Economics curriculum with the lesson plan facilitated teachers in integrating all educational resources, instructional tools, and evaluation methods with the learning activities, hence enhancing students' academic achievements.